Orthogonal control of mean and variability of endogenous genes in a human cell line - Alain R. Bonny (Nature Portfolio, 2021)
Stochastic fluctuations at the transcriptional level contribute to heterogeneity in isogenic cell populations. Here, the authors engineer TuNR which modulates the variability in gene expression of endogenous human genes independent of their mean expression.